2013
DOI: 10.11648/j.ijnfs.20130205.15
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Salmonella Carriage among Asymptomatic Food-Handlers in Southern Ethiopia

Abstract: Abstract:Background: Salmonella is the most frequently reported cause of food borne illness in Ethiopia. Objective: The aim of this study was to screen food handlers in the Dilla area of Southern Ethiopia and to assess the scale of carriage of Salmonella species and to offer prophylaxis followed by re-testing and advice on personal and food hygiene as appropriate. Method: Stool samples were collected from a total of 107 food handlers from various establishments in the area. Enrichment culture using Selenite br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 7 publications
6
20
2
Order By: Relevance
“…[7] ; Simsek Z et al 2010 Sanliurfa. [19] Studies showing almost similar carrier rate of Salmonella compared to our study (1%) were Bayeh et al [8] 2010 Bahir Dar Town, North West Ethiopia (1.85) Mulat Dagnew et al [32] 2013, Gondar University, North West Ethiopia (1.3%), Misganaw et al [33] 2013, Southern Ethiopia (0.93%) Gashaw et al [9] 2008 Gondar Town, North West Ethiopia and Lanata CF et al had reported zero percent Shigella infection. [30] among food handlers which was similar to our study.…”
Section: Agesupporting
confidence: 69%
“…[7] ; Simsek Z et al 2010 Sanliurfa. [19] Studies showing almost similar carrier rate of Salmonella compared to our study (1%) were Bayeh et al [8] 2010 Bahir Dar Town, North West Ethiopia (1.85) Mulat Dagnew et al [32] 2013, Gondar University, North West Ethiopia (1.3%), Misganaw et al [33] 2013, Southern Ethiopia (0.93%) Gashaw et al [9] 2008 Gondar Town, North West Ethiopia and Lanata CF et al had reported zero percent Shigella infection. [30] among food handlers which was similar to our study.…”
Section: Agesupporting
confidence: 69%
“…It is due to contamination of water, food, and poor sewage disposal system. The very young, elderly, and immunocompromized individuals are particularly more susceptible to Salmonella infections at a lower infective dose than healthy adults (8).…”
Section: Boydii ( Group C) and S Sonnei ( Group D) (1)mentioning
confidence: 99%
“…Contamination of equipment, utensils, and personal hygiene of food handlers help to spread Salmonella [813]. …”
Section: Introductionmentioning
confidence: 99%